Efektivitas Produk Afirmasi “Cheermail” Terhadap Peningkatan Iklim Kerja Positif Karyawan di PT. Baruga Asrinusa Development - Auralia M, Nurul; Fiqh, Salsabila; Tridinistari, Divka; Zainuddin, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this study was to evaluate the effectiveness of the affirmation product